2006
DOI: 10.1002/cncr.22199
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of severe menorrhagia in oncology patients with treatment‐induced thrombocytopenia by luteinizing hormone‐releasing hormone agonist and depo‐medroxyprogesterone acetate

Abstract: BACKGROUNDMenorrhagia is a serious complication in young female oncology patients who suffer from severe thrombocytopenia during myelosuppressive treatment. To the authors' knowledge, little is known regarding the incidence of this complication or the effectiveness of possible therapies for its prevention.METHODSIn this retrospective clinical study, after a thorough gynecologic evaluation, young female oncology patients with regular menstrual cycles undergoing myelosuppressive treatments received either depo‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
2
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 88 publications
1
50
2
7
Order By: Relevance
“…Furthermore, it may decrease thrombocytopenia-associated menorrhagia, as recently described [37]. Moreover, the recent studies of Recchia et al [25,26] and Del Mastro et al [27] supporting this cotreatment in breast cancer have shown that, in premenopausal women with early breast carcinoma, the addition of a GnRH agonist to adjuvant therapy and temporary total estrogen suppression in patients with estrogen receptor-positive disease was well tolerated, protected long-term ovarian function, and appeared to improve the expected clinical outcome [25,26].…”
Section: Gnrh Agonists As An Adjunct To Current Fertility-preserving mentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, it may decrease thrombocytopenia-associated menorrhagia, as recently described [37]. Moreover, the recent studies of Recchia et al [25,26] and Del Mastro et al [27] supporting this cotreatment in breast cancer have shown that, in premenopausal women with early breast carcinoma, the addition of a GnRH agonist to adjuvant therapy and temporary total estrogen suppression in patients with estrogen receptor-positive disease was well tolerated, protected long-term ovarian function, and appeared to improve the expected clinical outcome [25,26].…”
Section: Gnrh Agonists As An Adjunct To Current Fertility-preserving mentioning
confidence: 66%
“…The only significant difference was the rate of POF: Ͻ7% in the GnRH agonist cotreatment group versus Ͼ53% in the control (chemotherapy without the GnRH agonist) group [1, 4, 7, 10, 11, 14, 16 -19]. The relatively advanced age (35,37,40, and 40 years) of four of the five patients in the study group who developed POF (the fifth had oophorectomy for pelvic recurrence) suggests that minimizing follicular loss may be efficient only in young patients whose follicular reserve is above a certain limit. In patients older than 36, this reserve may not be sufficient.…”
Section: Gnrh Agonist Treatment In Cancer Patientsmentioning
confidence: 99%
“…Another study evaluated 101 premenopausal women undergoing myelo-suppressive chemotherapy who developed severe thrombocytopenia (platelet counts less than 25,000/ L). 6 This study group was on average older (mean age 29.8 8.8 years) than the previous study. The sample included 20 untreated patients who had a 40% incidence of lifethreatening bleeding requiring intervention.…”
Section: Discussionmentioning
confidence: 58%
“…Тем не менее на сегод-няшний день специфические факторы, стимулирую-щие выработку тромбоцитов, в широкой клинической практике отсутствуют. Переливание тромбовзвеси яв-ляется ограниченным методом и может быть ассоции-ровано с развитием осложнений [6,7]. У девочек, до-стигших полового созревания, следует помнить о высоком риске развития меноррагий в период тром-боцитопении после миелосупрессивных режимов ХТ.…”
unclassified
“…Геморрагические осложнения представляют 2-ю по частоте причину смертности у взрослых пациенток с лейкозом и другими онкологическими заболевания-ми, поэтому проблема профилактики гиперменореи высокоактуальна. Важно подчеркнуть, что девочки, достигшие полового созревания, до начала противо-опухолевого лечения должны быть консультированы врачом-гинекологом с целью оценки менструальной функции, данных ультразвукового исследования (УЗИ) органов репродуктивной системы, гормонального ста-туса [7].…”
unclassified